1987
DOI: 10.1515/bchm3.1987.368.2.937
|View full text |Cite
|
Sign up to set email alerts
|

46-kDa Mannose 6-phosphate-Specific Receptor: Biosynthesis, Processing, Subcellular Location and Topology

Abstract: Synthesis of the cation-dependent mannose 6-phosphate-specific receptor was followed in cells of human (fibroblasts, Hep G2 cells, U937 monocytes, blood-derived macrophages) or rat (Morris hepatoma 7777 cells), origin. The mature form of the receptor has an apparent molecular size of 46 kDa except in fibroblasts, where the apparent molecular size was 43 kDa. The receptor contains 7-8 N-linked oligosaccharide chains, about 5 of which are converted into endo -resistant forms within 2 h of synthesis. A small frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 1 publication
2
55
1
1
Order By: Relevance
“…Perdue et al (33) have reported that the M6P/IGF-II receptor is a monomer when solubilized, whereas Stein et al (34) suggested that it may exist as a dimer in the plasma membrane, as determined by cross-linking studies. The M6P/ IGF-II receptor was solubilized and purified from fresh bovine liver.…”
Section: Intermolecular Cross-linking Of M6p/igf-ii Receptors Is Respmentioning
confidence: 99%
“…Perdue et al (33) have reported that the M6P/IGF-II receptor is a monomer when solubilized, whereas Stein et al (34) suggested that it may exist as a dimer in the plasma membrane, as determined by cross-linking studies. The M6P/ IGF-II receptor was solubilized and purified from fresh bovine liver.…”
Section: Intermolecular Cross-linking Of M6p/igf-ii Receptors Is Respmentioning
confidence: 99%
“…Characterization of purified forms of the receptor by gel filtration and sucrose density gradient centrifugation has suggested that the receptor exists in solution in a monomeric form (17,18), whereas chemical cross-linking studies have demonstrated that the receptor forms aggregates in the membranes of intact cells (19). Recent observations, however, suggest that the IGF2R may bind multivalent Man-6-P-bearing lysosomal enzymes by forming an oligomeric receptor complex.…”
mentioning
confidence: 99%
“…Immunoprecipitated mCTSD was treated with 10 m-units of peptide N-glycosidase F (Roche Molecular Biochemicals, Mannheim, Germany) for 20 h at 37 mC [35].…”
Section: Other Methodsmentioning
confidence: 99%